SUBSTITUSI TEPUNG KETAN HITAM SEBAGAI PENGGANTI TEPUNG TERIGU PADA PEMBUATAN DIET COOKIES - Williana Ariani; miratia afriani (JURNAL MANAJEMEN KULINER, 2024)
Black glutinous rice flour is a staple ingredient for making Indonesian pastries which is widely used by the Indonesian people. The potential of black glutinous rice flour is its very high fiber content which is beneficial in preventing the risk of various types of diseases such as heart disease, diabetes, and helps facilitate digestion. In this study, researchers used black glutinous rice flour as a substitute for wheat flour. With the use of black glutinous rice flour, it can show the potential value of natural resources and healthier options as a substitute for wheat flour. The purpose of this study was to determine the difference and quality of the level of liking of diet cookies products through organoleptic tests according to predetermined sensory properties. The method used in this research is an experimental method with steps in the form of hedonic quality test and hedonic test. Sensory attributes that are referenced by panelists include color, aroma, taste, texture. Based on data processing and the results of hedonic and hedonic quality tests conducted by 8 trained panelists and 18 moderately trained panelists, it was found that diet cookies products with 40 and 60 black glutinous rice flour were liked both in terms of color, aroma, taste, and texture.